PENGARUH NET PROFIT MARGIN, CURRENT RATIO, FIRM SIZE, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2016- 2020) - Hafier Solana Wahyu Munir; Bambang Sudarsono (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The purpose of this study of this research is to determine the effect of Net Profit Margin, Current Ratio, Firm Size, Debt to Equity  Ratio, and Return  on Equity  partially and simultaneously on the Dividend Payout Ratio in Food and Beveragel Sub-sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX). 2016-2020 period. This research was conducted in a quantitative  descriptive manner using secondary data obtained on the Indonesia  Stock  Exchange (IDX). The  population  of this study is as many as 19 manufacturing companies in the  Food and Beverage  Sub- sector which are listed on the Indonesia Stock Exchange (IDX). The sampling method obtained as many as 13 companies in accordance with certain criteria. For testing using T test (partial) and F test (simultaneous). The results of the T test are known that Net Profit Margin, Current Ratio, Firm Size, Return on Equity partially have a significant effect on the Dividend Payout Ratio, while the Firm SIze partially has no significant effect on the Dividend Payout Ratio. While the results of the F test are known that Net Profit Margin, Current Ratio, Debt to Equity Ratio, and Return on Equity simultaneously have a significant effect on the Dividend Payout Ratio.